Measurement of visual ability in children with cerebral palsy: a systematic review. (21st April 2016) - Deramore Denver, Belinda; Froude, Elspeth; Rosenbaum, Peter; Wilkes‐Gillan, Sarah; Imms, Christine
Abstract : Aim: To identify and evaluate measures of visual ability used with children with cerebral palsy (CP). Method: Eight databases were searched for measures of visual ability. Key selection criteria for measures were: use with children with CP; focus of visual ability measurement at the Activities and Participation domain of the International Classification of Functioning, Disability and Health (ICF). The Consensus‐based Standards for the Selection of Measurement Instruments (COSMIN) Checklist was used to assess psychometric properties. Results: From 6763 papers retrieved, 25 were relevant and 19 measures of visual ability were identified. Only 10 measures were supported with evidence of validity or reliability. No discriminative measure analogous to existing CP functional classification systems was found. No outcome measure valid for evaluation of visual abilities of children with CP was found. Interpretation: Vision impairment is recognized as relevant to the functioning of children with CP; however, measurement of vision is most often focused at 'Body Function' levels, for example visual acuity. Measuring visual abilities in the Activities and Participation domain is important in considering how a child with CP functions in vision‐related activities. The lack of psychometrically strong measures for visual ability is a gap in current clinical practices and research. What this paper adds: A clear conceptual definition and framework for measuring visual ability is critical in furthering our understanding of the topic. No valid evaluative measures of visual ability were identified. There is no currently available measure of visual ability for children with cerebral palsy analogous to existing cerebral palsy functional classification systems.